Law Omission in Muslim Society: Inquiring Citizen Rights in the Administration of Islamic Family Law in Madura Indonesia - Syawqi, Abdul Haq; Umam, Muhammad Khatibul; Ridho, Achmad Ainur; Ilyas, Roziana Amalia; Subakti, Try (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Understanding on the law omission seems controversial; some view it only as an interruption of normal life, and some discern it as an administrative violation. Differences in the understanding may produce difficulties in enforcing the administration of Islamic family law. In line with this context, while mapping forms of the law omission in various community groups, this study analyses reasons for differences of the understanding of it. This study was based on data collected from interviews, FGDs and Google Forms on three different community groups with religious structural characteristics in 4 regencies on Madura Island. This study revealed that social differences and social classes in a society have become a force that structures the society’ views or understanding of the law omission. Differences of the understanding have consequences for the levels of difficulties in enforcing the Islamic family law, especially in the administrative context, such as in cases of registration and dispensation of marriages. Structural differences that exist in a religious society become important to differentiate factors in an interpretation of a reality of life. This paper suggests to expand the observed cases and to provide additional data sources to enable an in-depth and comprehensive understanding of the impact of the law omission in the field of administration of Islamic family law.